(untitled) (Medico Legal Update, 2020)
Objective: To assess the knowledge and perceptions of health care workers towards coronavirus (COVID-19) in most of the governorates of Iraq. Method: A cross-sectional survey, web-based study was conducted among HCWs about COVID- 19 during the last two weeks of April 2020. Knowledge and Perception were assessed by five components adapted from the Ebola knowledge scale, and A 7-item instrument this part was developed using WHO course materials on Emerging respiratory for viruses COVID-19 and distributed randomly to HCWs using social media. Descriptive statistics were used to express participants’ demographic information, mean knowledge score and mean Perception score of HCWs. Chi squares tests were used to assess the association between study variables and Perception questions was used to identify the level of association among variables at the significance level of p<0.05. Result: (184) participated of HCWs complete the survey (64.1%) are males, aged 20-29 years (54.3%), and most of them are Nurse (64.7%) and Lab-technicians (20.1%). Regarding COVID-19, most of them used social media to obtain the information (68%), About less than half of the respondents (41.30%) opined that COVID-19 was ? a severe illness transmitted to people from wild animals. Approximately 87% of respondents identified “contact by airborne droplets through breathing, sneezing or coughing” as the most common mode of transportation; Most of the participants associated COVID-19 with fever (90.80%), shortness of breath (89.10%) and coughing (76.66%). Handwashing and social distraction were chosen by most respondents (95.70%) as a method of preventing infection while 9.80% reported consuming gin, garlic, ginger, herbal mixtures and foods/soups as precautions against COVID-19. The majority of participants (81%) believed that COVID-19 is fatal; It was also noted that the social media (Whatsapp, Facebook, Instagram, Twitter etc.) are the most common source of health information about COVID-19 (65.20%). demonstrated a positive perception of prevention and control towards COVID-19. Most elements of Perception were significantly associated with gender and age at (P <0.05). Conclusions: The results of this study showed that healthcare workers have a good knowledge and positive Perception towards COVID-19. As the global threat of COVID-19 continues to emerge, it is critical to additional education interventions and campaigns are required for healthcare workers.